2014
DOI: 10.1111/avj.12150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of needle gauge used for venipuncture on automated platelet count and coagulation profile in dogs

Abstract: Venipuncture can be performed with a 21G, 23G or 25G needle to obtain blood from dogs for automated platelet count and PT/aPTT measurement without affecting the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…The pig industry was found to fall broadly into two categories: larger farms that were vertically integrated, purchased semen to introduce new genetic material and did not market through saleyards and smaller producers that regularly used saleyards to both purchase and sell pigs. This study compliments that written by Schembri et al, 5 published recently, who examined the demographics and practices of pig farmers trading at saleyards in eastern Australia. Although the two studies have different study populations, different aims and were conducted 6 years apart, where the results overlap the findings are consistent.…”
Section: Editorial Emergency Disease Planning and Preparednesssupporting
confidence: 71%
See 1 more Smart Citation
“…The pig industry was found to fall broadly into two categories: larger farms that were vertically integrated, purchased semen to introduce new genetic material and did not market through saleyards and smaller producers that regularly used saleyards to both purchase and sell pigs. This study compliments that written by Schembri et al, 5 published recently, who examined the demographics and practices of pig farmers trading at saleyards in eastern Australia. Although the two studies have different study populations, different aims and were conducted 6 years apart, where the results overlap the findings are consistent.…”
Section: Editorial Emergency Disease Planning and Preparednesssupporting
confidence: 71%
“…A prospective, observational, randomised clinical study included 20 clinically healthy dogs in which blood was collected from the jugular veins using 21G, 23G and 25G needles. 5 Results showed no difference in the automated platelet count or automated coagulation times for the different needle gauges used, suggesting that the results of venipuncture are not altered by needle size.…”
Section: Small Animalsmentioning
confidence: 86%
“…To our knowledge, no studies in other species have found any difference in PT on blood drawn with different needle sizes, 6,7 and the finding that PT is longer with smaller gauge needles is unexpected. In theory, using a smaller-diameter needle requires a higher vacuum, which will exert higher shear forces on the blood, and more activation of platelets and coagulation factors, potentially leading to a shorter PT.…”
Section: Discussionmentioning
confidence: 73%
“…6 In dogs, no differences were found in those variables when comparing 21, 23 and 25 G needles. 7 The recommended needle gauge used for venipuncture in human medicine is 21 G, when possible. 6 There are no evidence-based recommendations in feline medicine, but there have been suggestions in the literature to use 21 G needles.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that venepuncture with a higher gauge needle can reduce patient morbidity, by alleviating discomfort during blood collection and reducing the risk of subsequent haemorrhage. 16 Therefore, in feline patients, an ideal needle size should be selected for safer blood collection; this depends on factors such as patient size, patient cooperation and predisposition to haemorrhage.…”
Section: Discussionmentioning
confidence: 99%